2018
DOI: 10.1186/s12862-018-1294-y
|View full text |Cite
|
Sign up to set email alerts
|

Implications for introgression: has selection for fast growth altered the size threshold for precocious male maturation in domesticated Atlantic salmon?

Abstract: BackgroundMature male parr (MMP) represent an important alternative life-history strategy in Atlantic salmon populations. Previous studies indicate that the maturation size threshold for male parr varies among wild populations and is influenced by individual growth, environmental conditions, and genetics. More than ten generations of breeding have resulted in domesticated salmon displaying many genetic differences to wild salmon, including greatly increased growth rates. This may have resulted in domesticated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Over the past decade, we have conducted a number of pedigree-controlled studies on a multiple-generation experimental population of domesticated and wild Atlantic salmon and their crosses at the aquaculture facility owned by the Institute of Marine Research located in Matre, western Norway ( Solberg et al, 2013 , 2014 ; Ayllon et al, 2015 ; Harvey et al, 2016 , 2018 ; Glover et al, 2018 , 2020 ; Perry et al, 2019 ; Besnier et al, 2020 ). The reader is directed to these publications for full details regarding the standard rearing conditions experienced in this fish farm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, we have conducted a number of pedigree-controlled studies on a multiple-generation experimental population of domesticated and wild Atlantic salmon and their crosses at the aquaculture facility owned by the Institute of Marine Research located in Matre, western Norway ( Solberg et al, 2013 , 2014 ; Ayllon et al, 2015 ; Harvey et al, 2016 , 2018 ; Glover et al, 2018 , 2020 ; Perry et al, 2019 ; Besnier et al, 2020 ). The reader is directed to these publications for full details regarding the standard rearing conditions experienced in this fish farm.…”
Section: Methodsmentioning
confidence: 99%
“…Following the above-mentioned procedure, 97–99% of the offspring were unambiguously assigned to their family of origin. The laboratory conducting these analyses has extensive experience in DNA parentage testing ( Solberg et al, 2013 , 2014 ; Harvey et al, 2016 , 2018 ; Glover et al, 2018 ), and the full details regarding the markers used and their amplification conditions are available in these previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past decade, we have studied an experimental population of domesticated and wild Atlantic salmon and their crosses at the aquaculture facility owned by the Institute of Marine Research located in Matre, western Norway (Solberg et al 2013;Solberg et al 2014;Ayllon et al 2015;Harvey et al 2016;Glover et al 2018;Harvey et al 2018). The reader is directed to these publications for full details regarding the standard rearing conditions experienced in this fish farm.…”
Section: Experimental Crossesmentioning
confidence: 99%
“…Total DNA from all offspring and parents was purified using the Qiagen DNeasy Blood & Tissue Kit (Qiagen, Hilden, Germany) according to the manufacturer´s recommendations Microsatellite DNA parentage testing was used to unambiguously identify the pedigree of all individuals used in this study using the exclusion based method implemented in FAP (Taggart 2007). The laboratory conducting these analyses has extensive experience in DNA parentage testing (Solberg et al 2013;Solberg et al 2014;Harvey et al 2016;Glover et al 2018;Harvey et al 2018), and the full details regarding the markers used and their amplification conditions are available in these previous studies. In addition to microsatellites, a set of 116 genome-wide distributed SNPs were genotyped in all offspring and parents for the purpose of linkage mapping (see below).…”
Section: Genetic Analysis -Microsatellites and Snpsmentioning
confidence: 99%
“…A theoretical paper suggested that the escape of a growthenhanced fish could lead to the demise of natural salmon stocks [135,136] despite clear indications that this speculative extreme concern would not happen in nature [137] . The theory has been field tested with farmed Norwegian Atlantic salmon where the dire consequences have not occurred despite thousands of growth-enhanced salmon escaping from Norwegian net pens [138][139][140] . In nature only about 1/1000 to 1/10000 fish eggs reach sexual maturity.…”
Section: Concerns Of Transgene Spreadmentioning
confidence: 99%